Characterisation of methane sources in Lutjewad, The Netherlands, using quasi-continuous isotopic composition measurements. Issue 1 (1st January 2020) - Menoud, Malika; van der Veen, Carina; Scheeren, Bert; Chen, Huilin; Szénási, Barbara; Morales, Randulph P.; Pison, Isabelle; Bousquet, Philippe; Brunner, Dominik; Röckmann, Thomas
Abstract: Despite the importance of methane for climate change mitigation, uncertainties regarding the temporal and spatial variability of the emissions remain. Measurements of CH4 isotopic composition are used to partition the relative contributions of different emission sources. We report continuous isotopic measurements during 5 months at the Lutjewad tower (north of the Netherlands). Time-series of χ(CH4 ), δ 13 C-CH4, and δD-CH4 in ambient air were analysed using the Keeling plot method. Resulting source signatures ranged from −67.4 to −52.4‰ vs V-PDB and from −372 to −211‰ vs V-SMOW, for δ 13 C and δD respectively, indicating a prevalence of biogenic sources. Analysis of isotope and wind data indicated that (i) emissions from off-shore oil and gas platforms in the North Sea were not detected during this period, (ii) CH4 from fossil fuel related sources was usually advected from the east, pointing towards the Groningen gas field or regions further east in Germany. The results from two atmospheric transport models, CHIMERE and FLEXPART-COSMO, using the EDGAR v4.3.2 and TNO-MACC III emission inventories, reproduce χ(CH4 ) variations relatively well, but the isotope signatures were over-estimated by the model compared to the observations. Accounting for geographical variations of the δ 13 C signatures from fossil fuel emissions improved the model results significantly. The difference between model and measured isotopic signatures was larger when using TNO-MACC III compared to EDGAR v4.3.2 inventory. Uncertainties in the isotope signatures of the sources could explain a significant fraction of the discrepancy, thus a better source characterisation could further strengthen the use of isotopes in constraining emissions.